Epoxylathyrane Derivatives as MDR-Selective Compounds for Disabling Multidrug Resistance in Cancer - Reis, Mariana Alves; Matos, Ana M.; Duarte, Noélia; Ahmed, Omar Bauomy; Ferreira, Ricardo J.; Lage, Hermann; Ferreira, Maria-José U. (Frontiers in Pharmacology, 2020)
Background: Multidrug resistance (MDR) has been considered one of the major obstacles for a successful chemotherapy in cancer. The collateral sensitivity effect (CS) is among the most promising anti-MDR approaches. Epoxylathyrane derivatives 1-16 were obtained by derivatization of the macrocyclic diterpene epoxyboetirane A (17), a lathyrane-type macrocyclic diterpene isolated from Euphorbia boetica. Some of them were previously found to be strong P-glycoprotein (P-gp/ABCB1) efflux modulators. Purpose: The main goal was to develop lathyrane-type macrocyclic diterpenes with improved MDR-modifying activity, by targeting more than one anti-MDR mechanism. Study design/methods: In this study compounds 1-16 were investigated for their potential collateral sensitivity effect against gastric (EPG85-257), pancreatic (EPP85-181) and colon (HT-29) human cancer cells and their drug-resistant counterparts, respectively selected against mitoxantrone (EPG85-257RNOV; EPP85-181RNOV; HT-RNOV) or daunorubicin (EPG85-257RDB; EPP85-181RDB; HT-RDB). The most promising compounds (8, 15, and 16) were investigated as apoptosis inducers, using the annexin V/PI staining and the active caspase-3 assay. Results: The compounds were more effective against the resistant gastric cell lines, being the collateral sensitivity effect more significant in EPG85-257RDB cells. Taking together the IC50 values and the collateral sensitivity effect, the best results were obtained for compounds 8, 15 and 16. Epoxyboetirane P (8), with the strongest MDR-selective antiproliferative activity against gastric carcinoma EPG85-257RDB cells (IC50 of 0.72 µM), was found to be 10-fold more effective against this MDR subline than in parental drug-sensitive cells. The collateral sensitivity effect elicited by compounds 15 and 16 appeared to be by inducing apoptosis via caspase-3 activation. Structure-activity relationships of the compounds were additionally obtained through regression models to clarify the structural determinants associated to the collateral sensitivity effect. Conclusions: This study reinforces the potential of lathyrane-type macrocyclic diterpenes as leads for the development of MDR-modifying agents.